Exploitation of IoTs for PMU in Tethered Drone - Theerayod Wiangtong; P. Pookaiyaudom; Phaophak Sirisuk (My University, 2021)
This paper presents the implementation of IoT (Internet of Things) for monitoring and control in the tethered drone PMU (Power Management Unit) system. Traditionally, power source of a drone is from battery which causes the tradeoff between weight and flight time. To overcome this limitation, stationary tethered drones consume energy from a ground energy source thru light weighted power cords. Tethered drones' benefits are ideally suited for military uses such as border security and surveillance system, where day-night surveillance capabilities are crucial to monitoring perimeters. It can also be used for tactical communication, fast-deployed relay stations. Since a long operation time, monitoring and control power onboard becomes necessary. Using extra cords for communication will increase the airborne weight. This paper presents the exploitation of wireless IoT system for the tethered drone PMU system. It consists of the PMU-ground constantly delivering 4000W power to PMU-air for BLDC motors also various payloads. With additional IoT including Raspberry Pi, NodeMCUs and sensors, users at ground station can monitor voltage and current values in real-time, also can control MOSFET switches connected with loads onboard via PMU touch screen monitor or smart devices.
Keywords: UAV Applications and Optimization; IoT-based Smart Home Systems; Opportunistic and Delay-Tolerant Networks